2011
DOI: 10.1002/cjas.215
|View full text |Cite
|
Sign up to set email alerts
|

Employee Identities in Corporate Codes of Ethics: The Equal, Responsible, Subordinating, and Self‐Monitoring Employee

Abstract: The article invites the reader to engage in a critical perspective. It emphasizes the role of language in formal corporate documents and the discursive practices of language use. It presents the results of a study that analyzes the corporate codes of ethics of the German Dax30‐companies. The study conceives codes of ethics as texts deploying discursive practices in order to position the various actors addressed in the documents. Four distinct identities have been elaborated: the equal, the responsible, the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, studies of codes for companies that operate internationally find that codes do not address, and lack flexibility/adaptability in code content, to local laws, values and norms (Amaeshi and Amao 2009;Halff 2010;Svensson and Wood 2007). Examinations of the language (symbolic aspects) of code content find that codes reinforce corporate hierarchy with a top-down, authoritarian emphasis (Winkler 2011;2012;Munter 2013) and this is found also in a case study of a CCE in practice where Helin et al (2011) find that codes rather than being used as enabling instruments for enlightenment, instead can be used as instruments for domination. Forster et al (2009) also find imitative features for codes, especially for small companies, which copy large company code content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies of codes for companies that operate internationally find that codes do not address, and lack flexibility/adaptability in code content, to local laws, values and norms (Amaeshi and Amao 2009;Halff 2010;Svensson and Wood 2007). Examinations of the language (symbolic aspects) of code content find that codes reinforce corporate hierarchy with a top-down, authoritarian emphasis (Winkler 2011;2012;Munter 2013) and this is found also in a case study of a CCE in practice where Helin et al (2011) find that codes rather than being used as enabling instruments for enlightenment, instead can be used as instruments for domination. Forster et al (2009) also find imitative features for codes, especially for small companies, which copy large company code content.…”
Section: Discussionmentioning
confidence: 99%
“…2008). However, findings from studies examining the symbolic aspects of code content bring to light previously hidden evidence of connotations within CCEs to reinforce corporate hierarchy with a top-down, authoritarian emphasis (e.g., Winkler 2011Winkler , 2012Munter 2013). Over one-third of the content-oriented studies examine the context surrounding the codes.…”
mentioning
confidence: 99%
“…Along with these moral identity-building elements, it can be observed that organizational discourse strongly relies on values with strong moral connotations, e.g. trust and mutual respect (Winkler, 2011), sacrifice (Gagnon and Collinson, 2014), authenticity (Tomkins and Nicholds, 2017), commitment (Kuhn, 2006), justice (Jenkins and Delbridge, 2017), solidarity (Sewell and Barker, 2006), etc.…”
Section: Moral Trappingmentioning
confidence: 99%
“…Normative control is deemed compatible with new market realities (Wasserman and Frenkel, 2011; Winkler, 2011). Due to globalization, technological change, enhanced consumerism and the service sector, markets have become complex, uncertain and unstable for business organizations (Endrissat et al , 2016; Fleming and Sturdy, 2011; Gagnon, 2008; Morris et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A more positive experience of the environment is likely to be associated with greater organisation identification (Yang, Johnson, Zhang, Spector, and Xu, 2013). It is for this reason that Yang et al (2013) and Winkler (2012) noted that employees identification with their organisation may the influenced by the their perception of environment of ethnic diversity.…”
Section: Theoretical Development and Hypothesismentioning
confidence: 99%